FAKTOR- FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT - Lestari, Winda; Rizany, Ichsan; Setiawan, Herry (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2021)
ABSTRACT The low quality of service so that the level of patient satisfaction has not met the minimum service criteria, namely 95% which is influenced by several factors so that the degree of satisfaction is still low.Objective: to find out the factors that influence the satisfaction level of swamp patients in hospitalMethods: This study uses a literature review, from two electronic databases; Google Scholar and Garuda in the period 2010-2020 found ten literatures that match keywords.Results: The results of data synthesis in 10 journal articles 5 journal articles stated that the level of patient satisfaction was low due to ineffective communication, 4 journal articles stated that the level of satisfaction was low because of the quality of service, and 1 journal article stated that the level of patient satisfaction was low due to official scheduling.Discussion: Patient satisfaction with the quality of service provided by nursing personnel to clients while receiving hospital care, services, and nursing care received by patients is a form of professional service that can increase inpatient satisfaction and improve the quality of health services. Keywords: Patient, Hospitalization, Satisfaction Level.